Some Applications via Common Coupled Fixed Points in \(G\)-Metric Spaces With Altering Distance Functions - Reddy, G. Upender; Naresh, P.; Rao, B. Srinuvasa (Communications in Mathematics and Applications, 2023)
In this article, we give some applications to integral equations as well as homotopy theory via common coupled fixed point theorems in complete \(G\)-metric space which involve altering distance function is established. We also furnish an example which supports our main result. Our results extend, unify and generalize some existing results in the current literature.